DETERMINATION OF TILT AND AZIMUTH ANGLES OF SOLAR PANELS AT TANJUNGPURA UNIVERSITY SOLAR POWER PLANT USING PVSYST 7.3 SOFTWARE SIMULATION - Muhammad, Dustin; Hiendro, Ayong; Yandri, Yandri (Faculty of Engineering, Universitas Tanjungpura, 2024)
Solar Power Plant is a plant that uses solar energy as a renewable source and converts solar energy into electrical energy. To maximize the intensity of sunlight, solar panels need an optimal tilt angle to receive high sunlight intensity. This research aims to determine the optimal tilt angle of solar panels and azimuthal angle so that solar panels obtain maximum output energy. The type of solar panel used is the monocrystalline type with an installed power of 1.51 MW with a total of 2800 panels using a nominal panel power of 540 Wp and 12 units of 1.1 kW inverters. At the research location, Tanjungpura University Solar Power Plant with coordinates 0 °3'37.486